Genetic determinants of chronic obstructive pulmonary disease in South Indian male smokers. - Cholendra Arja; Rajasekhara Reddy Ravuri; Venugopal N Pulamaghatta; Krishna Mohan Surapaneni; Premanand Raya; Chandrasekhar Adimoolam; Kodanda Reddy Kanala (PLoS ONE)
The development of chronic obstructive pulmonary disease, upon exposure to tobacco smoke, is the cumulative effect of defects in several genes. With the aim of understanding the genetic structure that is characteristic of our patient population, we selected forty two single nucleotide polymorphisms of twenty genes based on previous studies and genotyped a total of 382 samples, which included 236 patients and 146 controls using Sequenom MassARRAY system. Allele frequencies of rs2276109 (MMP12) and rs1800925 (IL13) differed significantly between patients and controls (p = 0.013 and 0.044 respectively). Genotype analysis showed association of rs2276109 (MMP12) under additive and dominant models (p = 0.017, p = 0.012 respectively), rs1800925 (IL13) under additive model (p = 0.047) and under recessive model, rs1695 (GSTP1; p = 0.034), rs729631, rs975278, rs7583463 (SERPINE2; p = 0.024, 0.024 and 0.012 respectively), rs2568494, rs10851906 (IREB2; p = 0.026 and 0.041 respectively) and rs7671167 (FAM13A; p = 0.029). The minor alleles of rs1695 (G), rs7671167 (T), rs729631 (G), rs975278 (A) and rs7583463 (A) showed significant negative association whereas those of rs2276109 (G), rs2568494 (A), rs10851906 (G) and rs1800469 (T; TGF-β) showed significant positive association with lung function under different genetic models. Haplotypes carrying A allele of rs2276109, G allele of rs1695 showed negative correlation with lung function. Haplotypes carrying major alleles of rs7671167 (C) of FAM13A and rs729631 (C), rs975278 (G), rs7583463 (C) of SERPINE2 had protective effect on lung function. Haplotypes of IREB2 carrying major alleles of rs2568494 (G), rs2656069 (A), rs10851906 (A), rs965604 (C) and minor alleles of rs1964678 (T), rs12593229 (T) showed negative correlation with lung function. In conclusion, our study replicated the results of most of the previous studies. However, the positive correlation between the minor alleles of rs2568494 (A) and rs10851906 (G) of IREB2 and lung function needs further investigation.